Phase behavior of poly(3-hydroxybutyrate)/poly(3-hydroxybutyrate-co-3-hydroxyvalerate) blends - Conti D.S. (2007)
Miscibility, molecular interactions and crystallinity of blends of poly(3-hydroxybutyrate) [P(3HB)] with poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] were studied in this work. P(3HB)/P(3HB-co-3HV)-6%3HV blends were prepared by casting and characterized by differential scanning calorimetry (DSC) and X-ray diffraction (XRD). The results for the glass transition temperatures (Tg) and the melting temperatures (Tm) showed that most of the blends are miscible in amorphous and melting phases. A good agreement between values of experimental Tgs for miscible blends and those predicted by Fox equation was achieved. XRD analyses confirmed the crystallinity degrees found by DSC. Measurement of Tm depression for the blends allowed to determine the Flory-Huggins interaction parameter (χ12) using the Nishi-Wang equation. The value of χ12 obtained is negative, indicating miscibility of the components of the blends, which is in agreement with DSC experiments. © 2007 Elsevier B.V. All rights reserved.